The Impact of Using Some Tools to Learn the Freestyle and Backstroke at An-Najah National University Students - Rafe Rushdi Abu Salamh (My University, 2016)
The purpose of this study was to identify the Impact of an learning program using some tools to learn the freestyle and backstroke at An-Najah National University students . A total of (20) male student, were randomly divided into two experimental groups, One of The groups underwent the program by using tools (n=10) and the other underwent the program without using tools (n=10).The statistical analysis showed that there were a Significant differences (α ≤ 0.05) between the pre and post measurement for the first experimental group (using tools) in favor of the post measurement on (Slip on the abdomen, sliping on the back, legs blows on the abdomen) Where they achieved change rate reached (88.4% 0.209%, 50.8%), respectively. The results showed a significant differences at the level of significance (α ≤ 0.05) between the two measurements pre and post for in favor of post measurements (Not using the tools group) on variables (sliping on the abdominal, sliping on the back, and legs blows on the abdomen). The results also showed no statistically significant differences at the level of significance (α ≤ 0.05) between the two measurements pre and post for (using the tools group), on variables (legs blows on the back, freestyle 25 meters, and backstroke 25 meters), where it achieved rate of change variables reached (42.1%, 25.1%, 17.9%), respectively. The results also showed a statistically significant differences at the level of significance (α ≤ 0.05) in the post measurement between the two experimental groups, and in favor of group learning by using tools, and so on variables (Slip on the abdomen, sliding on the back, and legs blows on the abdomen), As there were no statistically significant differences at the level of significance (α ≤ 0.05) on variables (legs blows on the back, freestyle 25 meters, and back stroke 25 meters). The researcher recommended using tools to assist in learning swimming skills. Key Word: Plates buoyancy, Fins, Slip on the abdomen, legs blows on the back, freestyle (25) meters.

هدفت الدراسة التعرف إلى أثر برنامج تدريبي باستخدام بعض الأدوات المساعدة على تحسين الأداء في السباحة الحرة وسباحة الظهر لدى طلاب جامعة النجاح الوطنية، حيث أجريت الدراسة على عينة مكونة من (20) طالبا، تم تقسيمهم عشوائياً إلى مجموعتين، إحداهما خضعت للبرنامج التدريبي باستخدام الأدوات، والأخرى خضعت للبرنامج التدريبي دون استخدام الأدوات، حيث تكونت كل مجموعه من (10) طلاب، واستخدم الباحث المنهج التجريبي في تصميم المجموعتين التجريبيتين، نظراً لملاءمته لطبيعة هذه الدراسة وأهدافها. وقد أظهرت نتائج التحليل الإحصائي باستخدام الحزمة الإحصائية للعلوم الاجتماعية (SPSS) وجود فروق ذات دلالة إحصائية عند مستوى الدلالة (α ≤ 0.05) بين القياسين القبلي والبعدي لأفراد مجموعة التدريب باستخدام الأدوات، ولصالح القياس البعدي، وذلك على متغيرات: الإنزلاق على البطن، والإنزلاق على الظهر، وضربات الرجلين في الإنزلاق على البطن، حيث حققت تلك المتغيرات معدل تحسن وصل إلى (88.4٪، 209٪، 50.8٪) على التوالي. كما أظهرت النتائج عدم وجود فروق ذات دلالة إحصائية عند مستوى الدلالة (α ≤ 0.05) بين القياسين القبلي والبعدي لأفراد مجموعة التدريب باستخدام الأدوات المساعدة، وذلك على متغيرات: ضربات الرجلين على الظهر، والسباحة الحرة (25)م، وسباحة الظهر (25)م، حيث حققت تلك المتغيرات معدل تحسن وصل إلى (42.1٪، 25.1٪، 17.9٪) على التوالي. وأظهرت النتائج أيضاً وجود فروق ذات دلالة إحصائية عند مستوى الدلالة (α ≤ 0.05) بين القياسين القبلي والبعدي لدى أفراد مجموعة التدريب دون استخدام الأدوات المساعدة في متغيرات: الإنزلاق على البطن، والإنزلاق على الظهر، وضربات الرجلين في الإنزلاق على البطن). كما أشارت نتائج الدراسة إلى وجود فروق ذات دلالة إحصائية عند مستوى الدلالة (α ≤ 0.05) في القياس البعدي بين أفراد مجموعتي الدراسة، ولصالح مجموعة التدريب باستخدام الأدوات المساعدة، وذلك على متغيرات: الإنزلاق على البطن، والإنزلاق على الظهر، وضربات الرجلين في الإنزلاق على البطن، فيما أشارت النتائج إلى عدم وجود فروق ذات دلالة إحصائية عند مستوى الدلالة (α ≤ 0.05) في القياس البعدي بين أفراد المجموعتين التجريبيتين، وذلك على متغيرات: ضربات الرجلين على الظهر، والسباحة الحرة (25)م، وسباحة الظهر (25)م، وقد أوصى الباحث بضرورة استخدام بعض الأدوات المساعدة في تحسين الأداء في مهارات السباحة. الكلمات المفتاحية: لوحات الطفو، الزعانف، الزحف على البطن، ضربات الرجلين على الظهر، السباحة الحرة (25) متر.
أثر استخدام بعض الأدوات المساعدة على تحسين الأداء في السباحة الحرة وسباحة الظهر لدى طلاب جامعة النجاح الوطنية